Contribution of anti-cyclic citrullinated peptide antibody and rheumatoid factor to the diagnosis of arthropathy in haemochromatosis. Issue 9 (24th April 2007) - Aigner, E; Schmid, I; Österreicher, C H; Zwerina, J; Schett, G; Strasser, M; Niksic, F; Hohla, F; Ramsauer, T; Dorn, U; Patsch, W; Datz, C
Abstract : Objective: To investigate the prevalence of antibodies to cyclic citrullinated peptide (anti-CCP) and rheumatoid factor in patients with hereditary haemochromatosis (HHC) and to evaluate their diagnostic reliability in distinguishing HHC-associated arthropathy from rheumatoid arthritis. Methods: Anti-CCP antibodies and rheumatoid factor levels were determined by ELISA in sera from 87 patients with HHC homozygous for the C282Y mutation of the HFE gene, 31 patients with rheumatoid arthritis and 162 healthy controls. Results: Of the 87 patients with HHC, 32 (36.8%) had joint involvement. Anti-CCP antibodies were detected in only 1 patient (1.1%) with HHC, who had no joint disease, and in (1.2%) healthy controls. In total, 18 (58.1%) patients with rheumatoid arthritis displayed anti-CCP reactivity (p<0.001). Rheumatoid factor was detected in 10 (11.5%) patients with HHC compared with 7 (4.3%) healthy control subjects (p = 0.03) and 21 of 31 (65.6%) patients with rheumatoid arthritis. Conclusions: Testing for anti-CCP antibodies discriminates HHC arthropathy from rheumatoid arthritis, as these patients were consistently anti-CCP negative. Thus, HHC arthropathy should be considered in the differential diagnosis of CCP-negative arthritis.